Reduced risk of Efavirenz Discontinuation in Naïve Patients Starting First‐Line Antiretroviral Therapy with Single Tablet versus dual Tablet Regimen. Issue 5 (22nd September 2015) - Fabbiani, M; Zaccarelli, M; Latini, A; Sterrantino, G; D'Ettorre, G; Grima, P; Mondi, A; Rossetti, B; Borchi, B; Giuliani, M; Antinori, A; De Luca, A; et al.
Abstract : Objectives: Despite not being approved in Europe as first‐line therapy, the efavirenz (EFV)‐containing single tablet regimen (STR) is frequently used in clinical practice in naïve patients but few data are available on this strategy. In our study, we aimed to assess the risk of EFV discontinuation in patients starting antiretroviral therapy with STR vs . nonSTR. Methods: This was a multicentre study retrospectively enrolling naïve patients starting EFV+TDF+FTC. Patients were followed from the time of treatment initiation to the discontinuation of the EFV‐containing regimen, comparing STR vs . nonSTR. Two different analyses were performed: (A) nonSTR patients censored at the last observation (switch to STR not considered as the end of observation); (B) nonSTR patients censored at the time of switch to STR. Results: The study included 235 patients, of whom 74 (31.5%) directly started STR. Among patients starting nonSTR, 108 (67.1%) switched to STR after a median period of 6 months. Forty‐four EFV discontinuations were observed (13 among STR vs . 31 among nonSTR patients). The overall estimated probability of discontinuation was 30% at 5 years, about half (14.8%) of these occurring during the first year. Analysis A did not show significant differences between STR and nonSTR regarding the probability of efavirenz discontinuation (19.9% vs . 24.7% at 5 years, P = 0.630). In contrast, Analysis B showed that the probability of EFV discontinuation was similar (8.3%) between STR and nonSTR patients up to 8 months. Thereafter, a significantly higher rate of discontinuation was observed in nonSTR patients (47.5% vs . 19.9% at 5 years, P = 0.034). Conclusions: Our data suggest that an early switch to STR during the first months of treatment could reduce the risk of EFV discontinuation.